Cyber dating victimization in young people: Relationship with perceived stress, depression, suicidal ideation and sexting - Carrascosa, Laura; Ortega-Barón, Jessica; Iranzo, Begoña (Acciones e Investigaciones Sociales, 2025)
Cyber dating violence in young people has been linked to risky behaviors, such as sexting, and this relationship can have serious mental health implications. However, the predictive value of these variables in partner cybervictimization has not been explored in depth. This study analyzed partner cybervictimization in young people according to the intensity of bullying (moderate and severe), and its relationship with perceived stress, depression, suicidal ideation, sexting and sextortion. The sample consisted of 514 participants, 247 males (48.1%) and 267 females (51.9%) aged 18-30 years (M = 22.3; SD = 3.60). Nonparametric statistical analyses were performed, including Spearman correlations, one-way analysis of variance with Games-Howell post-hoc comparisons, and multiple linear regressions. Results showed a positive relationship between partner cybervictimization, perceived stress, depression, suicidal ideation, and sexting. Severe victims of cyberbullying and cyberaggression showed significantly lower scores on psychological adjustment compared to moderate and non-victims. Regarding sextortion, severe victims presented higher scores than non-victims. In addition, depressive symptomatology and suicidal ideation were predictors of cybervictimization by direct aggression and control, with sextortion standing out as a predictor of cybercontrol. These findings evidence the need for intervention programs that prevent cyberviolence and promote healthy couple relationships.
Keywords: Cyber violence by a partner; Technology; Youth; Stress; Suicide